Writing Indigenous Narratives Through Project-Based Learning: Promoting Students’ Critical Thinking in an EFL Classroom - Lestari, Indrie Setya; Nurnaningrum, Gayatri; Astuti, Indri Andriani; Hermawan, Hengki Anggra; Lugina, Tiana Dara; Amalia, Lulu Laela (International Journal of Language Education, 2025)
This study investigates how PBL enhances students’ critical thinking abilities as they compose narrative texts based on indigenous narratives in an English as a Foreign Language (EFL) classroom. The research conducted among 35 ninth-grade students (divided into seven groups) in a public junior high school in Bandung, Indonesia, using qualitative methods, including observation and document analysis, the study evaluates students' critical thinking through the Critical Thinking VALUE Rubric. Results indicate that PBL significantly promoted critical thinking, with students engaging in deeper reflection on cultural, ethical, and social issues in their narrative projects. High-Perceived Critical Thinking (HPCT) stories exhibited greater complexity and analysis than Low-Perceived Critical Thinking (LPCT) stories, which focused more on practical aspects. The PBL model can improve students' critical thinking skills, as evidenced by four out of seven groups falling into the High-Perceived Critical Thinking (HPCT) category. This study is significant because previous research has rarely combined culturally relevant content with structured critical thinking development in EFL contexts, creating a gap in effective instructional strategies. Therefore, it is recommended that EFL educators integrate culturally meaningful project-based tasks with explicit scaffolding to systematically nurture both critical thinking skills and language proficiency among learners.